Lived Experiences of Senior High School Teachers on Distance Learning Delivery Modalities: A Basis for Curriculum Planning Model - Rowena G. Caganan; Lerma P. Buenvinida (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
The study delved into the lived experiences of Senior High School teachers in utilizing distance learning delivery modalities in a province in the Philippines as basis for curriculum planning model. The researcher utilized the hermeneutic- phenomenological qualitative research design. The participants of the study were the sixteen (16) senior high school teachers including the researcher herself. Results of the study revealed that majority of senior high school teachers were teaching using modular distance learning. They could not freely offer a variety of teaching styles because of the absence of faceto-face interaction. Also, the following themes emerged based on the testimonies of the participants Utilization of DepEd-Initiated Learning Resources, Utilization Social Media and Free Online Applications. Unveritable Teacher-Learner Interaction and Feedbacking, Demanding Output Verification, Uncertain Students’ Learning, NonCompliance on Output Submission. Network Connectivity, Intensive Online Monitoring and Communication, and Perpetual Communication. These themes pertains to the challenges encountered by teachers in facilitating learning utilizing distance learning. It is recommended that there must be a provision of technical assistance to teachers and school leaders about distance learning delivery. School leaders may conduct schoolbased webinar training to teachers, learners, and parents regarding distance learning. Teachers may also pursue higher educational education and engage in professional learning ommunities to be well-equipped in the new normal. Moreover, the researcher recommended for the utilization of the R-J-C Curriculum Planning Model to improve the implementation of various learning delivery modalities in Laguna province.